مسلمة بن القاسم القرطبي: روايته وزياداته على كتاب "الأوائل" من مصنف ابن أبي شيبة : (Maslamah bin al-Qasim al-Qurtubi: His Narration and his Addition to the Book of “al-Awa'il” in Musannaf of Ibn Abi Shaybah) - (Baddreah Mohmmed Ibrahim AL-Hejji), بدرية بنت محمد بن إبراهيم الحجي (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract One of the most significant matters that the scholars of hadith “Ahl al-Hadith” were interested in is the addition of narrators from among their sheikhs. These additions were significant with the earlier scholars of Hadith due to their knowledge on the categories of the sheikhs. When the determination of who came later got weaken it was required to know, study and give the due attention to these additions and compile their biographies. This research aims to contribute in identifying the additions of the narrators, their types, knowing their ranks and criteria. The study is significant to differentiate between the hadiths which were in the book and the ones which have the additions of narrators since this was not originally being the condition in the original book for a hadith to be categorized as ‘ṣaḥīḥ”. This study will attend to the hadiths with such additions in the book and referring them from the books of sunnah in the aspects of their chains of narrators as well as their judged categories. The study is based on deductive critical method. Among the conclusions are: The necessity of complementing Hadith terminology’s sections by adding the information of the additions of narrators. The objective of most of those who added these narrators was to validate what they heard and convey the hadith without differentiating between what were agreed upon and what were not. Maslamah bin al-Qāsim had made a few additions to Muṣannaf of ibn Abi Shayba that reached seventeen in number. It is necessary to remind that the study of the books of narrations might contain certain additions that were not mentioned originally by the author of the book. Key words: Maslamah bin al-Qāsim al-Qurṭubī, biography, addition of narrators, addition to the book “al-Awā’il”, Ibn Shaybah, al-Muṣannaf, al-takhrīj.